Involving older people with multimorbidity in decision-making about their primary healthcare: A Cochrane systematic review of interventions (abridged). Issue 10 (October 2020) - Butterworth, J.E.; Hays, R.; McDonagh, S.T.J.; Bower, P.; Pitchforth, E.; Richards, S.H.; Campbell, J.L.
Highlights: Patient involvement in decision-making is key to delivering personalised care. Yet it was not measured for older patients with multimorbidity in primary care. There is a gap between the multimorbidity guidelines and the evidence base. We provide a conceptual model of the theory behind existing interventions. Transparency in intervention design with consistency in evaluation is still needed. Abstract: Objective: To assess the effects of interventions aimed at involving older people with multimorbidity in decision-making about their healthcare during primary care consultations. Methods: Cochrane methodological procedures were applied. Searches covered all relevant trial registries and databases. Randomised controlled trials were identified where interventions had been compared with usual care/ control/ another intervention. A narrative synthesis is presented; meta-analysis was not appropriate. Results: 8160 abstracts and 54 full-text articles were screened. Three studies were included, involving 1879 patient participants. Interventions utilised behaviour change theory; cognitive-behavioural therapy and motivational interviewing; multidisciplinary, holistic patient review and organisational changes. No studies reported the primary outcome 'patient involvement in decision-making about their healthcare'. Patient involvement was evident in the theory underpinning interventions. Certainty of evidence (assessed using GRADE) was limited by small studies and inconsistency in secondary outcomes measured. Conclusion: The evidence base is currently too limited to interpret with certainty. Transparency in design and consistency in evaluation, using validated measures, is required for future interventions involving older patients with multimorbidity in decisions about their healthcare. Practice implications: There is a large gap between clinical guidelines for multimorbidity and an evidence base for implementation of their recommendations during primary care consultations with older people.